Kemampuan Menulis Teks Prosedur Siswa Kelas XI SMA Negeri 1 Tambusai Utara - Syahrani, Melda; Alber, Alber (UIR Press, 2024)
Language ability is a person's ability to convey or communicate what is on his mind and his feelings to achieve the goals he wants to achieve. One of the language skills that students must master is writing skills that students must master is writing procedural texts. The research method used is the case study method. The type of research approach chosen by the researcher is a qualitative approach. The data collection techniques used in this research are observation and test techniques. Data analysis techniques in research are identification, grouping data, classifying the data according to the structural aspects and linguistic aspects contained in the procedural text, analyzing the data according to relevant theories, and concluding the results of the analysis. The results of the research found that the ability of 127 students in writing procedural texts in the structural aspect included Fair (C), 49 students were able to master writing procedural texts and 78 students were still unable to master writing procedural texts and students' ability in writing procedural texts was in the Good category. (B) 78 students were able to master writing correct procedural texts and 49 students still had not mastered the assessment indicators in the linguistic aspect.